Rural Women and their Roles in Tourism - Arzjani, Zahra; Rahiminezhad, Vida (International Journal of Bio-resource and Stress Management, 2023)
Rural development optimizes the poor conditions of villagers. It helps villagers to achieve self-sufficiency which is a part of entrepreneurial plan. One of the entrepreneurial aims is to achieve rural sustainability. For rural sustainability, it is necessary to pay attention to tourism, handicrafts and domestic productions that could reduce rural immigration to cities. Nowadays, tourism industry is growing, but the disappointment is that women in rural areas throughout the Iran are still leading a life of dependency that does not allow them to achieve positive economic and social status. This article examines the situation of rural women in tourism in Iran. The results show that rural tourism can be used as a tool to bring socio-economic development of the rural people in developing countries. However, if rural tourism is to be successful, the governments of developing regions must actively facilitate and encourage the expansion of women’s role in a systematic manner with institutional support..